Oral Health Promoting Behaviors of Diabetic Patients in Warin Chamrap District, Ubon Ratchathani Province: Pakin Chaichuay - Chaichuay, Pakin; Juntavaree, Peyanut (Princess of Naradhiwas University Journal, 2024)
This cross-sectional study aimed to investigate oral health-promoting behaviors and study factors related to oral health-promoting behaviors of 300 samples were diabetic patients in Warin Chamrap District, UbonRatchathani Province. Data collection was 5 - part questionnaires: 1) Personal characteristics, 2) oral health care knowledge and understanding testing, 3) oral health problem perception, 4) awareness of oral health care, 5) social support for oral health care, 6) oral health attitudes and beliefs, and 7) oral health promotion behavior. The content validity was 1.00, 0.94, 0.96, 0.94, 0.95, 0.98, and 0.97, respectively. KR-20 was 0.79. The reliability testing by Cronbach's alpha coefficient of questionnaire 3-7were 0.84, 0.76, 0.82, 0.77, and 0.76, respectively. Data analysis using frequency, percentage, mean, standard deviation, Chi-square and Fisher's exact test. The results of the study found that: 1) Oral health care behavior of diabetic patients was at a moderate level (M=2.97, S.D.= 0.57); knowledge and understanding of oral health care were at a moderate level (M=10.19, S.D.= 2.70); perception of oral health problems was at a moderate level (M=3.31, S.D.=0.68); awareness of oral health care was at a moderate level (M=3.05, S.D.=0.59); social support was at a moderate level (M=3.12, S.D.=0.58); and attitudes and beliefs regarding oral health were at a high level (M= 3.85, S.D.= 0.53). 2) Relationship factors found that personal characteristics such as age group were significantly related to oral health promotion behaviors of diabetic patients P<0.05 with a Chi-square value of 23.70. Gender, education level, occupation, and insulin exposure were not related. Knowledge and understanding of oral health care, awareness of oral health problems, and oral health attitudes and beliefs were significantly related to oral health promotion behaviors among diabetic patients P<0.05 with a Chi-square of 83.22, 16.40, and 9.92, respectively. Awareness of oral health care and social support was not related to oral health promotion behaviors among diabetic patients. Research results show that the age group of diabetic patients has knowledge and understanding of oral health. Recognition of oral problems and having an attitude of good faith will have behaviors that promote good oral health.